2021
DOI: 10.1039/d1fo02455h
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of mung bean coat against hyperlipidemia in mice fed with a high-fat diet: insight from hepatic transcriptome analysis

Abstract: The potential underlying mechanism of mung bean coat against hyperlipidemia was related to the activation of the PPAR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Collectively, our data suggest that dietary supplementation with the GPH could reduce the levels of TG, TC, LDL-c, AST and ALT and relieve hyperlipidemia and hepatic injury caused by HFD or HFD + DSS. Similar results were found in obese mice after dietary intervention with flaxseed powder, 11 banana pulp, 29 coarse cereals, 30 and mung bean hulls, 12 all of which are rich in dietary fiber and polyphenols.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Collectively, our data suggest that dietary supplementation with the GPH could reduce the levels of TG, TC, LDL-c, AST and ALT and relieve hyperlipidemia and hepatic injury caused by HFD or HFD + DSS. Similar results were found in obese mice after dietary intervention with flaxseed powder, 11 banana pulp, 29 coarse cereals, 30 and mung bean hulls, 12 all of which are rich in dietary fiber and polyphenols.…”
Section: Resultssupporting
confidence: 76%
“…Mung bean hulls were also found to inhibit weight gain in mice induced by HFD. 12 Liver weights were significantly increased in the HFD and DHFD groups of mice compared with mice in the CON group; however, GPH intervention at both doses significantly reduced the liver weight compared to the HFD and DHFD groups, especially the latter ( p < 0.05, Fig. 1D).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…RNA sequencing (RNA-seq) is applied to reveal the transcriptome profile of organisms or their cells under certain conditions, and this is widely used in the medical field to clarify the pharmacological mechanism of drugs, especially those with complex components and affecting multiple targets, such as Traditional Chinese Medicines (Chen et al, 2022;Wang, Qi, et al, 2021;Wang, Zhuang, et al, 2021). RNA-seq was shown to be appropriate to demonstrate properties of hypolipidemic agents at the transcriptional level: for example, Hou et al compared the transcriptome of diet-induced hyperlipidemic rats and those receiving treatment with mung bean coat, which demonstrated that the PPAR signaling pathway was affected by the treatment (Hou, Liu, et al, 2021). In another example, Tu et al ( 2019) investigated the lipid-lowering efficacy of red raspberry extract and used RNA-Seq to detect the underlying mechanisms, which identified 7 genes whose expression was closely related to the pharmacological property.…”
mentioning
confidence: 99%